A Randomised Clinical Study Comparing Conventional and Insulin Syringes for Local Anaesthesia in Primary Maxillary Teeth in Children - Abhimanyu Sharma; Kumar Rakshak Anand (Advances in Human Biology, 2026)
Abstract Introduction: Effective paediatric pain control through local anaesthesia (LA) is crucial, yet traditional syringes often induce anxiety. Insulin syringes, with their finer needles and less intimidating design, offer a promising alternative for reducing children’s pre-injection fear and discomfort through precise, slower delivery. Conversely, conventional syringes, while versatile, can heighten anxiety due to larger needles and rapid delivery. This article compares both methods’ clinical performance and acceptance in children. Materials and Methods: This crossover study enrolled 46 healthy 4–9-year-olds, naive to dental injections, requiring bilateral maxillary primary tooth extractions. Participants, showing positive cooperation and no contraindications, were randomised to receive LA through conventional then insulin syringe, or vice versa, with a 1-week washout. Results: Children’s self-reported pain faces pain scale–revised for LA and extraction showed no significant difference between conventional and insulin syringes. Observer-rated pain face, legs, activity, cry, and consolability was significantly lower with insulin syringes during LA but higher during extraction. Pulse rate and oxygen saturation showed no inter-group difference. Patients preferred insulin syringes slightly (56.52%), but not significantly. Conclusion: Insulin syringes caused less observed distress during LA, but both types yielded similar self-reported pain and effectiveness. Patient preference for insulin syringes was not significant.